The Effect of Digital Payment and E-Service Quality on Consumptive Behavior among Shopee Users - Anggorowati, Anggi; Sari, Dhany Efita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Individuals, as entities living on this earth, have a variety of needs that must be fulfilled in their lives. Because of the diversity of needs to be met, individuals are directly involved in consumption activities to ensure fulfillment. Often, the purchase of a commodity is not based on a real need, but on behavior carried out solely to satisfy personal pleasure, thereby resulting in the individual becoming consumptive. The factors causing consumptive behavior are the use of digital payment and e-service quality. Therefore, this study aims to examine the effect of digital payment and e-service quality on consumptive behavior among Shopee users. The study used a quantitative approach with a comparative causal design. The study population of all students at vocational high school 1 Pedan amounted to 1,063, and samples of 291 students were counted with the Slovin formula with a degree of significance of 5%. The sampling technique used stratified random sampling. The instruments used for questionnaires were shared through Google Forms. Data analysis techniques used multiple-linear regression. The results of the study showed that digital payment has a positive and significant effect on the consumptive behavior of Shopee users, e-service quality has a positive and significant effect on the consumptive behavior of Shopee users, and digital payment and e-service quality has a simultaneous and significant positive effect on the consumptive behavior among Shopee users. Taking into consideration the limitations of this study, future researchers are advised to explore additional variables that may affect consumptive behavior and broaden the sample size to obtain a more comprehensive overview.